The Role of Mathematical Connections in Mathematical Problem Solving - Pambudi, Didik Sugeng; Budayasa, I Ketut; Lukito, Agung (Mathematics Education Journal, 2020)
Problem-solving and mathematical connections are two important things in learning mathematics, namely as the goal of learning mathematics. However, it is unfortunate that the ability of students 'mathematical connections is very low so that it impacts on students' failure in solving mathematical problems. The writing of this paper aims to discuss the understanding of mathematical problems, mathematical problem solving, mathematical connections, and how they play a role in solving mathematical problems. The method used in writing this paper is a method of studying literature, which is reinforced by the example of a qualitative research result. The research subjects consisted of two eighth grade students of junior high school in Jember East Java, Indonesia, in 2017/2018. The research data consisted of written test results solving the mathematical problem as well as interview results. Data analysis uses descriptive qualitative analysis. From the results of literature studies and research results provide a conclusion that mathematical connections play an important role, namely as a tool for students to use in solving mathematical problems where students who have good mathematical connection skills succeed in solving mathematical problems well, while poor mathematical connection skills cause students to fail in solving mathematical problems.